ANALISIS PEMBENTUKAN TRUST PELANGGAN MELALUI KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TOKO SWALAYAN - Asakdiyah, Salamatun (Jurnal Analisis Bisnis Ekonomi, 2010)
This research aimed to test influence between service quality, customers satisfaction also interaction between service quality and customers satisfaction in the building of customers trust of Supermarket. This research efforted in Pamella supermarket in Yogyakarta. Sample categorized with sampling convenience method and purposive sampling. Data collection effored by giving list of question to the respondent that is contains about service quality, customer satisfaction and customer’s trust. This research use Moderator Regression Analysis. In the other side, T test and F tests are used to test asked hypothesis. The result of partially regression coefficient test with T test shows taht service quality, custoemer satisfaction also interaction betwee them influence significantly to customer’s trust. In the other side coefficient regression test’s result shows taht variables of service quality, customer’s satisfaction also interaction between them both influence to customer’s trust. Variables of service quality and customer’s satisfaction are able to explain customer’s trust variable up to 98,6% and the rest is 1,4% caused by another variable taht is not included in the research model.